VD_FINDINFO Jug / 2016 / 34 vom 25. Januar 2016 - VD Tribunal cantonal (2016)
SUSPENSION DE LA PROCÉDURE, ACQUITTEMENT, IN DUBIO PRO REO, CONSTATATION DES FAITS | 10 CPP (CH), 398 al. 3 let. b CPP (CH)